2023
DOI: 10.3389/fphar.2023.1257450
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals targeting glycolysis in colorectal cancer therapy: effects and mechanisms of action

Lu Zhan,
Fangting Su,
Qiang Li
et al.

Abstract: Colorectal cancer (CRC) is the third most common malignant tumor in the world, and it is prone to recurrence and metastasis during treatment. Aerobic glycolysis is one of the main characteristics of tumor cell metabolism in CRC. Tumor cells rely on glycolysis to rapidly consume glucose and to obtain more lactate and intermediate macromolecular products so as to maintain growth and proliferation. The regulation of the CRC glycolysis pathway is closely associated with several signal transduction pathways and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 237 publications
(276 reference statements)
0
2
0
Order By: Relevance
“…The role of enhanced aerobic glycolysis in accelerating uncontrolled proliferation of cancer cells is well-established. In CRC, aerobic glycolysis not only supplies nutrients for cell proliferation but also plays a regulatory role in metastasis, angiogenesis, cell differentiation and chemotherapy resistance ( 13 - 18 ). Hence, we further explored whether LINC01977 functioned as a regulator of aerobic glycolysis; the results revealed that LINC01977 facilitated aerobic glycolysis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The role of enhanced aerobic glycolysis in accelerating uncontrolled proliferation of cancer cells is well-established. In CRC, aerobic glycolysis not only supplies nutrients for cell proliferation but also plays a regulatory role in metastasis, angiogenesis, cell differentiation and chemotherapy resistance ( 13 - 18 ). Hence, we further explored whether LINC01977 functioned as a regulator of aerobic glycolysis; the results revealed that LINC01977 facilitated aerobic glycolysis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The first-line chemotherapeutic agents for CRC patients include 5-FU, irinotecan (IRT), oxaliplatin (OXA), and capecitabine. 31 …”
Section: Lncrna In Tumorigenesis and Chemotherapy Resistancementioning
confidence: 99%